A numerical investigation of the rotor blockage effect on cascade noise using a sliding mesh method. (23rd June 2021) - Ying, Wei; Fattah, Ryu; Zhong, Siyang; Zhang, Xin; Gea-Aguilera, Fernando
Abstract: The accurate evaluation of the broadband noise generated by fan wakes interacting with the outlet guide vanes (OGVs) in the aero-engines remains challenging due to the stochastic nature of sound and the complex flow conditions. A systematic study of the design parameters from full-scale and three-dimensional turbulence simulations is still expensive from a computational perspective. A simplified approach is to unwrap the fan blades and OGVs at a constant radial location to reproduce two-dimensional cascades. This approach assumes periodic boundary conditions at the upper and lower boundaries. For realistic cascades, there are relative motions between the rotating fan blades and stationary OGVs. The fan wakes are convected downstream towards the OGVs, and the turbulent wakes are distorted in the vicinity of the OGVs leading edge, which produce broadband noise. This paper aims at studying the upstream-travelling sound waves that is scattered by the solid surfaces of the fan blades, which alter the sound distribution. This scattering process is called the blockage or shielding effect, and it is influenced by the fan speed, blade geometry and spectral content of the sound. In this work, a synthetic turbulence method is employed to reproduce the fan wakes, and the Euler equations are solved to model the sound generation and propagation. An efficient sliding mesh method is developed to capture the physics due to the relative motions between the fan blades and OGVs. The numerical implementation is validated for various turbulence-cascade interaction configurations and the blockage effect due to the fan blades is studied in detail. A significant blockage effect due to a moving blade row on fan-OGV noise can be noticed on the acoustic power radiation. A decrease in sound power level (PWL) in the upstream direction is seen at low frequencies while an increase can be observed at high frequencies, which can be attributed to the sound power transfer between frequencies and modes. Both the effect of fan rotating speed and the rotor blade stagger angle are further tested and compared with the benchmark cases on the variation of PWL spectra and changes of acoustic modal distributions to study the impact of operation conditions and geometric parameters.